Effect of shading on physiological attributes and comparative transcriptome analysis of Camellia sinensis cultivar reveals tolerance mechanisms to low temperatures - Zaman, Shah; Shen, Jiazhi; Wang, Shuangshuang; Song, Dapeng; Wang, Hui; Ding, Shibo; Pang, Xu; Wang, Mengqi; Sabir, Irfan Ali; Wang, Yu; Ding, Zhaotang (Frontiers in Plant Science, 2023)
Tea is a vital beverage crop all over the world, including in China. Low temperatures restrict its growth, development, and terrestrial distribution, and cold event variability worsens cold damage. However, the physiological and molecular mechanisms of Camellia sinensis under shade in winter remain unclear. In our study, tea leaves were utilized for physiological attributes and transcriptome analysis in November and December in three shading groups and no-shade control plants. When compared to the no-shade control plants, the shading group protected tea leaves from cold damage, increased photochemical efficiency (Fv/Fm) and soil plant analysis development (SPAD), and sustained chlorophyll a, chlorophyll b, chlorophyll, and carotenoid contents by physiological mean. Then, transcriptome analysis revealed 20,807 differentially expressed genes (DEGs) and transcription factors (TFs) in November and December. A comparative study of transcriptome resulted in 3,523 DEGs and many TFs under SD0% vs. SD30%, SD0% vs. SD60%, and SD0% vs. SD75% of shading in November and December. Statistically, 114 DEGs were downregulated and 72 were upregulated under SD0% vs. SD30%. SD0% vs. SD60% resulted in 154 DEGs, with 60 downregulated and 94 upregulated. Similarly, there were 505 DEGs of which 244 were downregulated and 263 were upregulated under SD0% vs. SD75% of shading throughout November. However, 279 DEGs were downregulated and 105 were upregulated under SD0% vs. SD30%. SD0% vs. SD60% resulted in 296 DEGs, with 172 downregulated and 124 upregulated. Finally, 2,173 DEGs were regulated in December, with 1,428 downregulated and 745 upregulated under SD0% vs. SD75%. These indicate that the number of downregulated DEGs in December was higher than the number of upregulated DEGs in November during low temperatures. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses of differentially expressed genes were highly regulated in the photosynthesis, plant hormone signal transduction, and mitogen-activated protein kinase (MAPK) signaling pathways. However, qRT-PCR and RNA-seq relative expression of photosynthetic (DEGs) Lhcb2 in both November and December, plant hormone (DEGs) BRI1 and JAZ in November and IAA and ERF1 in December, and key DEGs of MAPK signal transduction FLS2, CHIB, and MPK4 in November and RBOH, MKK4_5, and MEKK1 in December in three shading groups and no-shade control plants responded to tea cold tolerance. The enhanced expression of light-harvesting photosystem I gene Lhca5, light-harvesting photosystem II gene Lhcb2, and mitogen-activated protein kinases MEKK1 and MPK4/6 enhance the cold-tolerance mechanism of C. sinensis. These comprehensive transcriptomic findings are significant for furthering our understanding of the genes and underlying regulatory mechanisms of shade-mediated low-temperature stress tolerance in horticultural crops.